Obtaining Journal Titles via Big Deals Most Cost Effective Compared to Individual Subscriptions, Pay-Per-View, and Interlibrary Loan - Reed, Kathleen (Evidence based library and information practice, 2016)
A Review of: Lemley, T., & Li, J. (2015). "Big deal” journal subscription packages: Are they worth the cost? Journal of Electronic Resources in Medical Libraries, 12(1), 1-10. http://dx.doi.org/10.1080/15424065.2015.1001959 Abstract Objective – To determine if “Big Deal” journal subscription packages are a cost-effective way to provide electronic journal access to academic library users versus individual subscriptions, pay-per-view, and interlibrary loans (ILL). Design – Cost-per-article-use analysis. Setting – Public research university in the United States of America. Subjects – Cost-per-use data from 1) journals in seven Big Deal packages, 2) individually subscribed journals, 3) pay-per-view from publishers’ websites, and 4) interlibrary loans. Methods – The authors determined cost-per-use for Big Deal titles by utilizing COUNTER JR1 metric Successful Full-Text Article Request (SFTAR) reports. Individual journal subscription cost-per-use data were obtained from individual publishers or platforms. Pay-per-view cost was determined by recording the price listed on publishers’ websites. ILL cost-per-use was established by reviewing cost-per-article obtained from libraries outside of reciprocal borrowing agreement networks. With the exception of pay-per-view numbers, title cost-per-use was averaged over a three-year period from 2010 through 2012. Main Results – Cost-per-article use for journals from Big Deals varied from $2.11 to $9.42. For individually subscribed journals, the average cost-per-article ranged from $0.25 to $84.00. Pay-per-view charges ranged from $15.00 to $80.00, with an average cost of $37.72. Conclusion – The authors conclude that Big Deals are cost effective, but that they consume such a large amount of funds that they limit the purchase of other resources. The authors go on to outline the options for libraries thinking about Big Deal packages. First, libraries should keep Big Deal packages in place if the average cost-per-article is less than individual subscriptions. Second, libraries could subscribe only to the most-used journals in Big Deals, cancel the packages, and rely on ILL and pay-per-view access. Third, consortia could be joined to favourably negotiate Big Deal package prices. Fourth, Big Deals could be dropped completely. Fifth, individual libraries armed with JR1 reports can negotiate with publishers for better deals.